Sodobni socialni in etnični procesi med koroškimi Slovenci - Zupančič, Jernej (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
The article discusses Slovene minority in Austria in the light of contemporary social, economic and spatial processes. Minority is subject to obvious regression of minority functions despite the open border and high hopes for improved attitude of Austrian state and provincial policy towards minority issues. The article points out that reasons of these processes should above all be sought inside the minority ethnic body: in its receptive abilities and characteristics of organization.
Keywords: Austria; Avstrija; narodne manjšine; koroški Slovenci; Carinthian Slovenes; čezmejno sodelovanje; politična geografija